Scientific Validity of Efficacy of Homoeopathic Treatment Modality for Underactive Thyroid - Hypothyroidism (Homoeopathy for All, 2023)
Hypothyroidism (Also Known As  Underactive Thyroid) Is A State In  Which The Thyroid Gland Does Not  Make Enough Thyroid Hormone.  Since The Main Purpose Of Thyroid  Hormone Is To “Run The Body’s  Metabolism”, It Is Understandable  That People With This Condition  Will Have Symptoms Associated  With A Slow Metabolism. This  Article Provides An Overview  of The Aetiology, Diagnosis,  And Appropriate General &  Homoeopathic Management of  Underactive Thyroid.
Keywords: Hormone; Hypothyroidism; Homoeopathic